Processos identitários em contextos de ações afirmativas - Silvia Adriana da Silva (2008)
This paper is the outcome of a previous research whose primary purpose was to comprehend the identity processes experienced by young black people, Considering their insertion in a context of recognition and appreciation of the negritude. In this sense we have developed a study in which the processes that involve the constitution of the subjects from their notions of racial origin and recognition, as well as some political activism, have offered the oportunity of problematization and analysis of the nature of our reality. Taking identity as an analytical category and defining it as a process characteristically dynamic, historical and political, we have tried to identify the conditions and the symbolical and concrete contexts that allow transformation and constitution of the subjects, always from the racial approach. Supported by the theoreticalreferences of the Social Psychology, we have analysed the course of two exscholarshipers from the Program of Affirmative Actions, in the FederalUniversity of Minas Gerais (UFMG), before and after they joined the program, trying to understand how these two women have established and transformed themselves through the experience of discriminations and subjections, and how they have been able to invent energetic and creative ways to face and resist those practices. In their process of signification of social reality and constitution of themselves, these women have attested the temporary and precarious character of the constructed identifications, and the need, always present, for new negotiations and cultural-political-economical-social-emotional articulations to consecute this process.